Exploring Current Evidence on the Past, the Present, and the Future of the Heart Team: A Narrative Review - Alexandru Burlacu; Adrian Covic; Mircea Cinteza; Paula Madalina Lupu; Radu Deac; Grigore Tinica (Cardiovascular Therapeutics)
Introduction. Including healthcare professionals dealing with cardiovascular diseases, Heart Team is a concept/structure designed for selecting diagnostic strategies, facilitating therapeutic decisions, and improving cardiovascular outcomes in patients with complex heart pathologies, requiring input from different subspecialties and the necessity of a multidisciplinary approach. The aim of this narrative review is to search for and to summarize current evidence regarding Heart Team and to underline the future directions for the development of this concept. Methods. We searched the electronic database of PubMed, SCOPUS, and Cochrane CENTRAL for studies including Heart Team. Forty-eight studies were included, if reference was made to Heart Team structure and functionality. Results. We depicted the structure and the timeline of Heart Team, along with actual evidence-based recommendations from European Guidelines. We underlined the importance of quality of knowledge-sharing and decision-making inside the Team, analyzing bad decisions which did not reflect members’ true beliefs due to “uniformity pressure, closed mindedness, and illusion of invulnerability.” The observation that Guidelines’ indications regarding Heart Team carry a level C indication underlines the very future of this Team: randomized controlled trials proving solid benefits in an evidence-based world. Conclusions. Envisioned as a tool for optimizing the management of various complex cardiovascular pathologies, Heart Team should simplify and facilitate the activity in the cardiovascular ward. Finally, these facts should be translated into better cardiovascular outcomes and a lower psychological distress among Team participants. Despite all future changes, there must always be a constant part: the patient should remain at the very center of the Team.